2016
DOI: 10.1080/00952990.2016.1191505
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use and viral suppression in persons receiving medical care for HIV-infection

Abstract: Background Marijuana use is common among persons living with HIV (PLWH), but its effect on HIV clinical outcomes has not been thoroughly studied. Objectives We determined the association between marijuana use and HIV viral suppression among PLWH. Methods Data came from five repeated cross-sections (2009 – 2013) of the Florida Medical Monitoring Project, a population-based sample of PLWH in Florida. Data were obtained via interview and medical record abstraction. Weighted logistic regression models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 45 publications
7
25
0
Order By: Relevance
“…Consistent with our results, a recent longitudinal cohort study of illicit drug users with HIV in Vancouver found no association between daily marijuana use and treatment adherence in multivariable analysis [16]. Similarly, in a recent analysis of a Florida cohort of PWH, no relationship between marijuana use and HIV outcomes was observed [10]. It is important to emphasize that, like the other two, very recent negative studies, our sample includes individuals in care at a time with simpler, less toxic ART regimens which may in part account for their good treatment outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with our results, a recent longitudinal cohort study of illicit drug users with HIV in Vancouver found no association between daily marijuana use and treatment adherence in multivariable analysis [16]. Similarly, in a recent analysis of a Florida cohort of PWH, no relationship between marijuana use and HIV outcomes was observed [10]. It is important to emphasize that, like the other two, very recent negative studies, our sample includes individuals in care at a time with simpler, less toxic ART regimens which may in part account for their good treatment outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…A multicenter cohort of HIV infected patients receiving care in 8 US cities between 2013–2015 found 31.6% of patients reported marijuana use during the past 3 months [9]. In a recent Florida sample of PWH in care, 20% reported recent marijuana use with 7% reporting daily use [10]. With these elevated levels of marijuana use among PWH receiving care, there is need to better characterize the relationship between marijuana use and HIV treatment outcomes, controlling for the frequent comorbidity with alcohol and other illicit drug use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to prior studies that report no significant or clinically meaningful differences in HIV viral load (44,45) or CD4+ cell count among marijuana users (4648) as compared to non-users. Yet others have found significantly lower HIV viral load (49,50) and higher CD4+ count (49) in marijuana users, although these studies differ methodologically as well as in the samples included.…”
Section: Discussionsupporting
confidence: 89%
“…The first cross-sectional study examined VL among individuals who met DSM-IV criteria for cannabis dependence versus non-dependent cannabis users and non-users, and found that dependent users (who reported slightly more than daily use, on average) were significantly more likely to have a detectable VL, compared with the non-dependent users (who reported < daily use, on average), or the non-users (Bonn-Miller et al, 2014). Contrastingly, and more in line with the presently recorded findings, in the second cross-sectional study, which was conducted among a representative sample of patients on HIV treatment in the state of Florida, daily cannabis use was not significantly associated with viral suppression (Okafor et al, 2016). In the RCT, no significant differences were found in short-term change in mean VL between participants randomized to smoke cannabis (3.95% tetrahydrocannabinol daily), ingest dronobinol (2.5 mg daily), or ingest a placebo daily (Abrams et al, 2003).…”
Section: Discussionsupporting
confidence: 55%